FINDING, PREPARING AND TRAINING FOOTBALL REFEREES - Constantin Gh (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Football has surpassed the status of being a social phenomenon at a national and international scale for a long time, as it is the new "religion of the 21st century" which brings together game practitioners under its scope regardless of religion, skin colour, geographical area, culture, philosophy, gender, age which has been proven by the number of members in more than 200 FIFA member national federations. As stated in the FIFA status, "each FIFA member shall organize football games by the Laws of the Game promulgated by the International Board which has complete and exclusive jurisdiction to modify them. Football game rules bring together a set of laws under which a game, game relations and player relations must take place, actually being the single criterion to assess players" behaviour as permissible or impermissible. Football game management is provided by referees. A referee guarantees that a competition shall take place according to the Laws of the Game. However, arbitration work in football is not a profession in every sense of the word, but a social function that a person with a specific training performs regularly at various football competitions for children, youth and pros. As in any purposeful and social value activity, football arbitration too requires the set-up of a scientifically based system of recruitment, selection, training, promotion. This system requires a certain way of combining and providing theoretical training, physical training, and psychological/mental training of referees. A referee plays an important role in modern football. Therefore, a referee must be trained, selected and protected from various influences (clubs, league, political field).